Cryptographic Protocol Synthesis and Verification for Multiparty Sessions - Bhargavan, Karthik; Corin, Ricardo; Denielou, Pierre-Malo; Fournet, Cédric; Leifer, James J. (Proceedings of the 22st IEEE Computer Security Foundations Symposium (CSF 2009, 2009)
We present the design and implementation of a compiler that, given high-level multiparty session descriptions, generates custom cryptographic protocols. Our sessions specify pre-arranged patterns of message exchanges and data accesses between distributed participants. They provide each participant with strong security guarantees for all their messages. Our compiler generates code for sending and receiving these messages, with cryptographic operations and checks, in order to enforce these guarantees against any adversary that may control both the network and some session participants. We verify that the generated code is secure by relying on a recent type system for cryptography. Most of the proof is performed by mechanized type checking and does not rely on the correctness of our compiler. We obtain the strongest session security guarantees to date in a model that captures the executable details of protocol code. We illustrate and evaluate our approach on a series of protocols inspired by web services.